Study on drug utilization pattern in conservative management of patients with pancreatitis in a tertiary care teaching hospital - P., Mohanraj; S., Abinaya; K., Shalini; G., Gopalakrishnan; K., Ravichandran (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Drug utilization plays a key role in helping the healthcare system to understand, interpret and improve the prescribing, administration and use of medications. The objective of the study was to assess the drug utilization pattern of drugs prescribed in conservative management of pancreatitis patients in a tertiary care teaching hospital. Methods: This prospective observational study was conducted in department of surgery, Rajah Muthiah Medical College and Hospital, Annamalai University. The study period was six months from November 2019 to April 2020. A total of 115 patients were selected based on inclusion and exclusion criteria. Results: The study population containing of 90% (n=104) males and 10% (n=11) females were included in the study. Most of the patients between age group of 25-44 years (48%). The most common etiology was alcoholic 68% (n=78). 7% of population with comorbidities (5% hypertension, 2% diabetes mellitus). In analgesics, tramadol (28%) and in antibiotics cefotaxime 21% was most prescribed. Lactated ringer solution (36%) was prescribed most as intravenous hydration. 7% (n=8) and 3% (n=4) of patients receiving enteral nutrition and parenteral nutrition. The average number of drugs per prescription was 8.5. Out of 1205 drugs, 61% of drugs prescribed in generic form, 39% were prescribed in brand name. The study analyzed that 69% of drugs were prescribed from essential drugs list (EDL) 2019 and 84% drugs prescribed from national list of essential medicines (NLEM) 2015. Number of prescriptions with injection were 79.07%. The overall antibiotic encounter rate 15%. Prescribed daily dose/defined daily dose (PDD/DDD) ratio of folic acid was 5. Conclusions: Drug utilization study can help in evaluating the quality of care given to the pancreatitis patients and promote rational use of medicines.